DEVELOPMENT OF AN ENVIRONMENTAL POLLUTION SCIENCE MODULE USING THE 4D MODEL INTEGRATED WITH ISLAMIC VALUES AND SDGs - Khoriyah, Fara Ainul; Noor, Faiq Makhdum (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
This research aims to develop a science learning module based on the Sustainable Development Goals (SDGs), integrated with Islamic values on environmental pollution material for junior high school students. The research method used is the Research and Development method with the 4D model (Define, Design, Develop, Disseminate), but the research was only conducted up to the Develop stage. The research population consisted of all 7th-grade students at MTs NU Assalam Kudus, totaling 214 students, with a sample of 16 students selected randomly (random sampling). The product trial resulted in an average score of 93.65%, categorized as very feasible for use. The module has undergone development stages, including Define, Design, and Develop, and was validated by material and media experts, with a material expert CVI score of 0.625 and a media expert CVI score of 0.863. The trial results showed positive responses from students and teachers, with an average score of 93.65%, indicating high feasibility for use in learning. This module provides a learning approach that integrates environmental pollution understanding with Islamic values and SDGs principles, aiming to raise students' awareness about the importance of environmental sustainability as part of their responsibility as khalifah on Earth.